Is the growth of marine copepods limited by food quantity or quality?. Issue 3 (28th April 2021) - Anderson, Thomas R.; Hessen, Dag O.; Mayor, Daniel J.
Abstract: Understanding what limits the growth of marine copepods is important for modeling food web dynamics and biogeochemical cycles in the ocean. We use a state‐of‐the‐art stoichiometric model that explicitly represents metabolic physiology to examine the roles of food quantity vs. quality in limiting the growth of these animals. The model predicts that the crossover from C‐ to N‐limitation occurs at food C : N 7.3–11.5 mol C mol N −1, depending on food quantity. Thus, despite significant losses of N in metabolism, copepods should be limited by C when consuming food at Redfield C : N (6.625). We nevertheless suggest that copepods do not seek C‐rich diets per se. Rather, results indicate limitation by food quantity as growth increases with organic matter intake, regardless of its elemental composition. Our work highlights the benefit of developing mechanistic representations of zooplankton metabolism in order to increase confidence in the predictions of biogeochemical models.